URGENSI PENDIDIKAN ANTI KORUPSI PADA SEKOLAH MENENGAH KEJURUAN MELALUI SOSIALISASI - I. P. Rasmadi; I. K. Tjukup; D. G.P. Yustiawan; I.D. G.D. Sugama (Buletin Udayana Mengabdi, 2022)
This community service aims to socialize the urgency of anti-corruption education in the teaching and learning process which emphasizes the application of anti-corruption values and principles. This activity provides an understanding of the importance of studying and understanding the values and principles of anti-corruption as a preventive effort in eradicating corruption. This community service uses field data (field research) to find out the symptoms that occur in the community then uses library data (library research) in finding service materials related to anti-corruption values and principles then activities are carried out using the lecture method which ends with a discussion. As a result of this activity students gain new knowledge about preventive measures to eradicate corruption that they can apply in the school, home and community environment, besides that teachers also understand their plans as agents of change who are able to develop psychologically their students with systemic education related to eradicating corruption. Participants are motivated to apply anti-corruption values and principles in the school environment. Keywords: Schools, anti-corruption, education.